KEBIJAKAN REDAKSIONAL DALAM KONVERGENSI MEDIA (Studi Kasus Media Online Sajiansedap.com pada Kompas Gramedia Group) - Farah Karsetia Sabillah (2020)
The presence of online media that relies on the internet turns out to have a major impact on other conventional media, especially print media which have begun to tumble in the face of competition with new media and changes in the lifestyle of people who are all digital. So, do not be surprised if many conventional media prefer to converge for survival in the digital era like today, one of which is Sajiansedap.com. However, convergence also changes the way journalists work in making news. In this study, the author tries to answer questions about the process of media convergence practices at Sajiansedap.com with other online media in the Kompas Gramedia media group and the extent to which media convergence practices for the benefit of the media business can be done but do not violate journalistic ethics. This research is qualitative research and uses case studies in Sajiansedap.com online media. Data collection techniques used were document studies, observations, and interviews. The results showed that Sajiansedap.com in searching for information for news, one of them by taking news from online media that was still in the Kompas Gramedia group media without any conditions. This has become a convergence policy that exists in order to answer the challenges of online media that are so fast in achieving the effectiveness of information distribution. The similarity of information with the media of one group, but this is not a form of plagiarism. In this study, the authors hope that people need to read news from various media so that they get information from different points of view.